Two year experience of a catheter-free, radio telemetric, oesophageal pH-monitoring (Bravo®) system in children at a single UK tertiary centre. (24th May 2012) - Rao, N; Campbell, DI; Narula, P; Taylor, C; Thomson, M; Rao, P
Abstract : Background: Introducing a catheterless form of oesophageal ph-monitoring to a younger or more challenging child has now become possible. The BRAVO® pH-system is a significant advancement in the evaluation of patients with gastroesophageal reflux because of better tolerability. Aims: To evaluate performance, tolerability, safety and day-to-day variability in acid reflux patterns in using the BRAVO® pH-system. Methods: Retrospective review of database and case notes of all children that underwent BRAVO® pH-capsule placement from June'09 to August'11 was done. All the capsules were deployed 4-6 cm proximal to the Z-line of the oesophagus under the influence of general-anaesthesia and under endoscopic vision. The data from the capsules were recorded by radio-telemetry onto the pH-boxes and uploaded onto a computer designated for this purpose. The paired-t-test was used to analyse the pH-values from 2 sub-groups (group 1 with 24 hour recordings and group 2 with 48 hour recordings). Results: 203 consecutive patients (122 male) of median age 9 (2-18 years) had the procedure. The youngest child weighed 9.29 kg. Successful pH data over 24 hours was obtained in 93.6% of patients and over 48 hrs in 59% of patients. Commonest indications were reflux symptoms (45%), abdominal pain (33%) and regurgitation (19.5%). In 12% of our patients with an underlying behaviour disorder the wireless pH study was preferred over a standard naso-oesophageal probe for compliance reasons. The other common indication in our centre was assessment of pre and post fundoplication, with 7 of the results indicating need for surgical management (3 laparoscopic and 4 endoscopic full thickness fundoplication). Nearly all studies (86%) were performed off acid-suppressing medications. A failure rate of 6.4%(13/203) was noted. Of the 13, 4 failed to detach from the introducer, 8 capsules detached within 1 hour of deployment and other failed due to recording-box error. There was no statistical difference between the pH-measurements of the first 24 hours with the 48-hour measurements (p=0.56). No adverse events were noted in any of our patients. Conclusions: The BRAVO® pH system is a safe and effective method of recording oesophageal acid exposure. It is an acceptable alternative for children who are particularly unwilling or unable to tolerate nasopharyngeal pH-catheter. Our results support the use of pH measurement for a period of 24 hours only.